Metody geofizyczne w procesie poszukiwania ukrytych zwłok - Adamiec, Jacek; Zdeb, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
In this article, the author presents how to use geophysical research to look for corpses. During the search, the following methods can be used: GPR, magnetic and metal detector, which assists in the detection of graves and mass graves. Research can be con-ducted as part of forensic archaeology and prosecutor’s proceedings. This article presents the possibilities and limitations of these methods.
Keywords: archeologia sądowa; georadar; wykrywacz metali; magnetometria